The impact of ecosystems on human health and well-being: A critical review. (July 2015) - Martinez-Juarez, Pablo; Chiabai, Aline; Taylor, Tim; Quiroga Gómez, Sonia
Abstract: Human health is a key factor for population well-being, and depends on the conditions and functioning of the ecosystem and its ability to provide adequate and healthy flows of ecosystem services, as stated by the well-known approach of the Millennium Ecosystem Assessment (MEA). The aim of this paper is to provide an overview of the literature focusing on the links between ecosystem services and human well-being, starting from a reinterpretation of the MEA framework. In this process, we highlight the need to consider the mechanism of exposure through passive, consumptive and active behaviour, as well as contextual factors such as socio-economic, demographic and climatic factors. In this context, tourism, recreation and leisure are linked to active engagement. The literature at present uses different measures of health and well-being, which suggests the need to develop harmonized approaches and new methods to assess the influence of study design on measured outcomes. In conclusion, the analysed studies show moderate evidence towards a positive impact of green environment, though positive and significant effects are not found in all cases examined.